1989
DOI: 10.1271/bbb1961.53.3127
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gum arabic and pectin on the emulsification, the lipase reaction, and the plasma cholesterol level in rats.

Abstract: Gumarabic, a widely used emulsifier, stabilized the substrate of lipase in an emulsion of oil and enhanced the lipase reaction. Pectin, a well-known gelling agent, destabilized the emulsion, and decreased the plasma levels of cholesterol in rats. Little effect of gum arabic on the cholesterol concentration of plasma and liver was observed. These findings might indicate the differences between the effects of gum arabic and pectin on the stability of emulsification and the activity of lipase in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…It is thus possible that the butyrate content in the cecum was also involved in the reduction of the serum TG content in the HK group, partly by suppressing absorption of fat in this study. Moreover, it is reported that some dietary fibers affected lipase activities by the change of emulsion stability in vivo and in vitro (16,18). This effect of dietary fibers is possibly associated with absorption of TG in this study.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…It is thus possible that the butyrate content in the cecum was also involved in the reduction of the serum TG content in the HK group, partly by suppressing absorption of fat in this study. Moreover, it is reported that some dietary fibers affected lipase activities by the change of emulsion stability in vivo and in vitro (16,18). This effect of dietary fibers is possibly associated with absorption of TG in this study.…”
Section: Discussionsupporting
confidence: 53%
“…These data may support the idea that more IDPS exists in BM and HK pulps than in the ␣-corn starch in the control diet, and might be involved in the excretion of the bile acids. It is suggested that suppression of micellar solubility of cholesterol or micelle formation lead to a decrease in serum cholesterol by some elements of foods such as soy protein peptic hydrolysate (17) and pectin (18). Interaction between the indigestive fraction derived from potato pulps and micelle formation is possibly involved in excretion of the bile acid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some polyphenols (e.g., naringenin) decrease the carotenoid uptake by Caco-2 cells . In the same way, diets rich in pectins avoid micelle formation during digestion; the oil emulsion is embedded in a gel-like pectin. , The rheological properties of pectins could increase the viscosity of the duodenal medium and impair the activities of lipase and bile acids. In humans, clinical studies have highlighted the negative effect on carotenoid bioavailability of diets rich in pectins. , …”
Section: Introductionmentioning
confidence: 99%
“…We have reported that the incorporation of lipids into a gel matrix of SDFs 3 ) and the repression of lipase activity by pectin 4 ) were responsible for lowering the plasma cholesterol level in rats. 5 ) Short-chain fatty acids (SCFAs) produced by colonic bacteria are related to the cholesterol level. 6) Dietary fibers are not digested by enzymes in the digestive tract,7) but they are consumed by colonic bacteria.…”
mentioning
confidence: 99%